Mitophagy defects arising from BNip3 loss promote mammary tumor progression to metastasis. (31st July 2015) - Chourasia, Aparajita H; Tracy, Kristin; Frankenberger, Casey; Boland, Michelle L; Sharifi, Marina N; Drake, Lauren E; Sachleben, Joseph R; Asara, John M; Locasale, Jason W; Karczmar, Gregory S; Macleod, Kay F
Abstract BNip3 is a hypoxia‐inducible protein that targets mitochondria for autophagosomal degradation. We report a novel tumor suppressor role for BNip3 in a clinically relevant mouse model of mammary tumorigenesis. BNip3 delays primary mammary tumor growth and progression by preventing the accumulation of dysfunctional mitochondria and resultant excess ROS production. In the absence of BNip3, mammary tumor cells are unable to reduce mitochondrial mass effectively and elevated mitochondrial ROS increases the expression of Hif‐1α and Hif target genes, including those involved in glycolysis and angiogenesis—two processes that are also markedly increased in BNip3‐null tumors. Glycolysis inhibition attenuates the growth of BNip3‐null tumor cells, revealing an increased dependence on autophagy for survival. We also demonstrate that BNIP3 deletion can be used as a prognostic marker of tumor progression to metastasis in human triple‐negative breast cancer (TNBC). These studies show that mitochondrial dysfunction—caused by defects in mitophagy—can promote the Warburg effect and tumor progression, and suggest better approaches to stratifying TNBC for treatment.